SERENDIPITOURS - Parada, Maria Enriqueta Saenz, 1968- (2017)
This paper presents the analysis of my design work which I titled Serendipitours. Serendipitours is a model for alternative trekking tours and nature experiences in the highlands that allows local sheep farmers to benefit from today’s growing nature tourism in Iceland while respecting local nature and the local traditional sheep farming trade. The model was conceived as a recipe, a replicable scalable tool, that aims at creating synergies between first and foremost local nature, non-human factors, as well as the needs of sheep farmers during their activities in the yearly sheep farming cycle, but can also be shaped by human factors such as the farmer’s knowledge, cooperation with other farmers, available technology, the visitor and other. The model is also the basis of an ideation tool that could be used to conceive and eventually prototype and test alternative trekking tours and nature experiences in highland areas. Such ideation tool can be used in workshops that could be offered by tourism agencies looking to promote product development in rural highland among sheep farmers interested in benefitting from the current tourism development in Iceland.